(untitled) (International Journal of Physiology, 2019)
Background Chronic obstructive pulmonary disease (COPD) is a major public health problem leading to high health care utilizations, poor health-related quality of life, and substantial cost burden and deaths worldwide. Aim To assess the peak expiratory flow rate (PEFR) and absolute eosinophil count (AEC) in COPD patients. Method This observational study was carried out among 80 COPD patients, volunteers referred from Medicine department of Santhiram Medical College. PEFR recorded was correlated with eosinophils. Results The mean PEFR value was 214.7 ± 49.39 and mean absolute eosinophil count value was 749.7 ± 152.01. There was strong negative significant correlation (?0.80) between PEFR and absolute eosinophil count (p < 0.05). Conclusion The findings indicated that whenever the blood parameter eosinophils increased, there was a decrease in the PEFR in COPD patients.